2005
DOI: 10.1007/s11192-005-0248-5
|View full text |Cite
|
Sign up to set email alerts
|

Signals in science - On the importance of signaling in gaining attention in science

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 26 publications
1
91
1
1
Order By: Relevance
“…Van Dalen and Henkens (2005) reported that the status of uncitedness of a paper becomes a stigma and the longer a paper is uncited, the lower its quality and the less inclined researchers will be to cite it. Glänzel et al (2003) reported that the probability of a paper's uncitedness increases dramatically with belated first citations, and the probability of being frequently cited later on decreases to the same extent.…”
Section: Extraction Of Papers' Quality Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Dalen and Henkens (2005) reported that the status of uncitedness of a paper becomes a stigma and the longer a paper is uncited, the lower its quality and the less inclined researchers will be to cite it. Glänzel et al (2003) reported that the probability of a paper's uncitedness increases dramatically with belated first citations, and the probability of being frequently cited later on decreases to the same extent.…”
Section: Extraction Of Papers' Quality Featuresmentioning
confidence: 99%
“…The social view stated that the various social factors in the communication process of papers, such as the status of the authors and the prestige of the journals in which they are published, are essential to determine their citation activities. Various features were identified from papers' scientific communication process (Fu and Aliferis 2010;Gilbert 1977;Laband and Piette 1994;Van Dalen and Henkens 2005).…”
mentioning
confidence: 99%
“…According to Dalen and Henkens (2005), the scientific quality of a publication can be determined not only based on the number of citations but also based on citation speed:…”
Section: Introductionmentioning
confidence: 99%
“…They found that 0.3% of those papers that were cited more frequently than 15 times in total were not cited between 1980 and 1984; van Raan found that only 41 of the articles from the ISI Citation Indexes published in 1988 received at most ten citations during the first ten years after publication and subsequently between 21 and 30 citations in the next four years. Other studies of delayed recognition include those of GARFIELD [1980] and GLÄNZEL & GARFIELD [2005] and other studies of sleeping beauties include those of VAN DALEN & HENKENS [2005] and BURRELL [2005].…”
Section: Introductionmentioning
confidence: 99%